Developing a Mobile Application Using Open Source Parking Management System on Etherium Smart Contracts. (December 2020) - Imbugwa, Gerald; Mazzara, Manuel; Distefano, Salvatore
Abstract: In this paper, we envision to illustrate the process to be used in developing a mobile application on the smart contract. We start by looking at what other researchers have accomplished and how we can improve on what already exists. The paper highlights the requirement gathering process, the methodology for data collection to streamline and validate the requirement, the architecture and implementation phase by analyzing the technological stack to achieve the business goal.